Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/w12030806
|View full text |Cite
|
Sign up to set email alerts
|

Managing Water Quality in Intermittent Supply Systems: The Case of Mukono Town, Uganda

Abstract: Intermittent water supply networks risk microbial and chemical contamination through multiple mechanisms. In particular, in the cities of developing countries, where intrusion through leaky pipes are more prevalent and the sanitation systems coverage is low, contaminated water can be a public health hazard. Although countries using intermittent water supply systems aim to change to continuous water supply systems—for example, Kampala city is targeting to change to continuous water supply by 2025 through an exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In contrast, first flush samples averaged an HPC concentration of 4.3 × 10 4 MPN/100 mL (4.3 ± 2.8 × 10 4 MPN/100 mL) and were significantly higher than concentrations from stable IWS (Kruskal–Wallis, p < 0.001) which averaged 70 ± 109 MPN/100 mL and ranged from 5 to 300 MPN/100 mL. Other studies have also found a deterioration of water quality during first flush events when supply is restarted regardless of the duration of the stoppage; 15–17,64–66 although differences in water quality between first flush and stable supply may not be significant in all cases. 16…”
Section: Resultsmentioning
confidence: 89%
“…In contrast, first flush samples averaged an HPC concentration of 4.3 × 10 4 MPN/100 mL (4.3 ± 2.8 × 10 4 MPN/100 mL) and were significantly higher than concentrations from stable IWS (Kruskal–Wallis, p < 0.001) which averaged 70 ± 109 MPN/100 mL and ranged from 5 to 300 MPN/100 mL. Other studies have also found a deterioration of water quality during first flush events when supply is restarted regardless of the duration of the stoppage; 15–17,64–66 although differences in water quality between first flush and stable supply may not be significant in all cases. 16…”
Section: Resultsmentioning
confidence: 89%
“…This study was conducted in Kampala, the capital city of Uganda with a water supply service covering an area of about 300 km 2 with a total pipe length of approximately 3,587 km of various sizes ranging from DN50 to DN700 (Sakomoto et al 2020). The pipe network was laid in 1929.…”
Section: Study Area Detailsmentioning
confidence: 99%
“…Pressure control allows network operators to minimize leakage [2] and reduce probability of pipe failures [3]. Furthermore, disinfectant residuals in WDNs are critical control variables to preserve water quality and eliminate the risks of pathogen contamination, with chlorine being a commonly used water disinfectant -see for example [4], [5]. Pressure control schemes are implemented by installing and operating pressure reducing valves (PRVs), which control pressure at their downstream node.…”
Section: Background and Motivationmentioning
confidence: 99%